2013
DOI: 10.1007/s13277-013-1208-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction among Caveolin-1 genotypes (rs3807987/rs7804372), H. pylori infection, and risk of gastric cancer in a Chinese population

Abstract: Caveolin-1, a candidate tumor suppressor, interacts with a number of transducing molecules and plays a regulatory role in several signaling pathways. Recently, a study revealed that Cav-1 G14713A (rs3807987)/T29107A (rs7804372) polymorphisms might be associated with the susceptibility to certain cancers. In this study, we evaluated the interaction among Caveolin-1 genotypes (rs3807987/rs7804372) and Helicobacter pylori infection and increased risk of gastric cancer among the Chinese population. Blood specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…There was no association between any of the other tested SNPs and ESCC risk. These results were consistent with other studies of CAV1 genetic polymorphism-related susceptibility to breast, colorectal and gastric cancers (Liu et al, 2011;Yang et al, 2010;Zhang et al, 2014). There was also an ethnic difference in the frequencies of genetic polymorphisms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was no association between any of the other tested SNPs and ESCC risk. These results were consistent with other studies of CAV1 genetic polymorphism-related susceptibility to breast, colorectal and gastric cancers (Liu et al, 2011;Yang et al, 2010;Zhang et al, 2014). There was also an ethnic difference in the frequencies of genetic polymorphisms.…”
Section: Discussionsupporting
confidence: 92%
“…To date, many studies have explored the association of functional polymorphisms of CAV1 with the susceptibility to oral (Bau et al, 2011), breast (Liu et al, 2011), colorectal (Yang et al, 2010), gastric (Zhang et al, 2014) and hepatocellular (Hsu et al, 2013) cancers. For ESCC, several previous studies have reported clinical impact of CAV1 expression in esophageal carcinoma by immunohistochemical or cDNA expression array analysis, indicating a statistically significant increased expression of CAV1 mRNA and protein levels (Hu et al, 2001;Kato et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies indicated that CAV1 G14713A polymorphism was associated with cancer risk, such as esophageal squamous cell carcinoma, gastric cancer, hepatocellular carcinoma, and breast cancer. 9 , 10 , 12 , 16 Other studies demonstrated that CAV1 G14713A polymorphism was not associated with the risk of cancer, including prostate cancer and nasopharyngeal carcinoma. 14 , 15 To provide a more detailed overview of the association, five genetic models were used in the current meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 presents the detailed process of selecting and excluding studies. In the 13 articles, all studies were case-control studies with the following SNP distribution: 11 articles were about polymorphism rs1997623 [19][20][21][22][23][24][25][26][27][28][29], 11 articles were about rs12672038 [19][20][21][22][23][24][25][26][27][28][29], 10 articles were about rs3757733 [19,[21][22][23][24][25][26][27][28][29], 12 articles were about rs3807987 [18][19][20][21][22][23][24][25][26][27][28][29], 9 articles were about rs3807992 [18,19,[21][22]…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…More than 20 SNPs in the CAV-1 promoter were detected in different types of cancers, some of which were thought to be genetic risk factors [17,18]. Six SNPs (rs1997623, rs3807987, rs12672038, rs3757733, rs7804372, and rs3807992) were most frequently studied among Asians.…”
Section: Introductionmentioning
confidence: 99%